x → 0 + lim k = 1 ∑ ∞ k ln ( x ) cos ( k x ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great approach! Thanks for sharing these ideas of now to manipulate power series in interesting ways.
Nice! And I'll have to start referring to L'Hôpital's rule as Bernoulli's rule out of respect to its true founder. :)
Log in to reply
When I went to college back in Switzerland, they referred to it diplomatically as the "rule of Bernoulli-de L'Hôpital" ;)
It's a matter of mind over money, or vice versa.
Log in to reply
Sir, so what is the difference between Bernoulli's rule and L Hopital's rule??
Why do you set as the right hand limit only ( x → 0 + )? The left hand limit and the right hand limit equals to − 1 , no?
Problem Loading...
Note Loading...
Set Loading...
As Brian Charlesworth observed in his solution to an earlier problem , k = 1 ∑ ∞ k e i k x = − ln ( 1 − e i x ) for 0 < x < π . Taking real parts and recalling that R e ( ln ( z ) ) = ln ∣ z ∣ , we find that k = 1 ∑ ∞ k cos ( k x ) = − ln ∣ 1 − e i x ∣ = − ln ( 2 sin ( x / 2 ) ) To prove the last equation geometrically, consider the triangle in the Argand plane with its vertices at 0, 1, and e i x . Finally x → 0 + lim k = 1 ∑ ∞ k ln ( x ) cos ( k x ) = − x → 0 + lim ln ( x ) ln ( 2 sin ( x / 2 ) ) = − x → 0 + lim sin ( x / 2 ) ( x / 2 ) cos ( x / 2 ) = − 1 by Bernoulli's rule (often mistakenly referred to as L'Hôpital's rule).